Prevention of anaemia in inner city toddlers by an iron supplemented cows' milk formula. Issue 1 (July 1996) - Daly, A; MacDonald, A; Aukett, A; Williams, J; Wolf, A; Davidson, J; Booth, I W
Abstract : There are few data to support the use of follow-on formulas in infants from the age of 6 months. In a prospective trial in a deprived inner city area of Birmingham 100 infants who were already receiving pasteurised cows' milk by 6 months of age were enrolled and randomised either to receive a follow-on formula or to continue on cows' milk from 6 months until 18 months. At 18 months of age the follow-on formula group returned to cows' milk and both groups were followed up until 24 months. Iron status, growth, and nutritional status were analysed at intervals of six months. At enrollment, no differences in haematological status were evident. However, by 12 months of age, 31% of the cows' milk group were anaemic (haemoglobin concentration < 110 g/l) compared with only 3% of those receiving follow-on formulas. At 18 months, 33% of the cows' milk group were anaemic compared with only 2% of the follow-on formula group and by 24 months of age none of the follow-on formula group was anaemic, whereas 26% in the cows' milk group still had a haemoglobin of < 110 g/l. Mean corpuscular volume was significantly smaller and ferritin significantly lower in the cows' milk group at 12, 18, and 24 months. Dietary iron intake was higher in the follow-on formula group at 12 and 18 months but not at 24 months, when both groups were back on cows' milk. Infants and toddlers at high risk of iron deficiency are therefore unlikely to become anaemic if receiving a follow-on formula, although the relative merits of follow-on formula compared with an ordinary infant formula remain uncertain.